Molecular Medicine - Nalbantoglu, Sinem; Amri, Hakima (IntechOpen, 2019)
Molecular medicine is an applied science focused on human genes/transcripts, proteins, metabolites, and metabolic networks that describes molecular and cellular processes of health and disease onset and progression. Molecular medicine-based integrative identification and characterization of biomarker targets and their clinical translations is essential to explain/decipher the mechanism(s) underlying physiological pathways and pathological conditions, and acquire cell-targeted early interventional and therapeutic strategies in the context of precision medicine and public health. Principally, Molecular Medicine provides an overview of the latest headlines/developments of systems and molecular medicine, highlighting the emerging high-throughput technologies, promising potential applications, and progress in biomedical research and development strategies.